UJI VIABILITAS BENIH PADA BEBERAPA VARIETAS PADI LOKAL GORONTALO - Megasari, Ria; Rasyid, Asmuliani; Darmawan, M.; Mutia, A. Khairun (Program Studi Agroteknologi, Fakultas Sains dan Teknologi, Universitas Muhammadiyah Siddenreng Rappang, 2024)
Paddy is the main food crop in Indonesia, including in Gorontalo Province, which has various local varieties. These varieties generally have the advantage of adapting to local environmental conditions, but sometimes they have not been scientifically tested regarding the quality of their seeds. This research aims to determine the level of seed viability of several local Gorontalo paddy varieties. This research was structured in a completely randomized design consisting of 6 treatments, namely the temo variety, maraya variety, pulo kuku variety, red pulo variety, sonu variety and ponda variety. Each treatment was repeated 3 times to obtain 18 treatment combinations. The research data were then analyzed statistically using analysis of variance (ANOVA). The results showed that the Temo variety gave the best results on seed viability in terms of germination parameters (100%) and a growth speed index of 50. Meanwhile, the Sonu variety gave the best results in terms of germination rate (1.97 days) and radicle length (9.23 cm ). And overall the local Gorontalo variety rice seeds have very good quality as seen from the seed germination capacity reaching 95 – 100%.